2021
DOI: 10.2174/1871530320999200818103709
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Extracted from Asteriscus graveolens Improve Glucose Metabolism and Lipid Profile in Diabetic Rats

Abstract: Aim: This study aimed to evaluate the antidiabetic and antihyperlipidemic effects of Asteriscus graveolens. Background: Asteriscus graveolens (Asteraceae) is a medicinal plant widely used by the Moroccan population to treat various diseases including diabetes. Objective: This work aimed to assess the capacity of flavonoids extracted from Asteriscus graveolens (FEE) to improve diabetes mellitus and dyslipidemia in normal and STZ-induced diabetic rats. Methods: Flavonoids were extracted from A. graveolens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These findings are consistent with earlier research. Li C. et al demonstrated the instability of the diabetic hepatic glycogen structure [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with earlier research. Li C. et al demonstrated the instability of the diabetic hepatic glycogen structure [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are extremely useful in treating diabetes and diabetic complications. They can exert their therapeutic effects on diabetes by enhancing insulin secretion, regulating glucose metabolism, and reducing inflammation and oxidative stress [ 76 , 77 , 78 ].…”
Section: Classification Synthesis and Activity Of Flavonoidsmentioning
confidence: 99%
“…Recently phenylpropanoids have been reported to prevent post-prandial hyperglycemia and type 2 diabetes mellitus by promoting glucose uptake ( Yoshioka et al, 2022 ). Studies have illustrated several benefits of specific dietary natural antioxidants on DM: reducing apoptosis, promoting proliferation of β cells, alleviating oxidative stress, inhibiting α-glucosidase activity, and increasing insulin production ( Babu et al, 2013 ; Wang et al, 2019 ; El-Ouady et al, 2021 ) [17–19]. Therefore, antioxidants from cinnamon extract could be developed into drugs used for DM management.…”
Section: Introductionmentioning
confidence: 99%